Effect of Cu(BDC-NH2) MOF deposited on Cu/Cu2O electrode and its better performance in photoelectrocatalytic reduction of CO2 - Silva, Beatriz Costa e [UNESP]; Irikura, Kallyni [UNESP]; Frem, Regina Célia Galvão [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2021)
The present work reports the development of Cu/Cu2O-Cu(BDC-NH2) electrode, prepared by electrochemical deposition using the ligand 2-amino-1,4-benzenedicarboxylic acid and copper ion (II) produced in situ, and its application in CO2 reduction in aqueous medium. The Cu(BDC-NH2) MOF deposited on Cu/Cu2O electrode act as efficient catalyst for the photoelectrocatalytic reduction of CO2 due to its high surface area and high capacity of trapping CO2. Under optimized conditions and based on the application of the proposed electrode, the photoelectrocatalytic reduction of 0.1 mol L−1 sodium sulfate saturated with CO2 under UV–Vis irradiation and applied potential of +0.1 V can generate an amount of approximately 674 μmol L−1 of methanol in 3 h of treatment. The amine substituent in Cu(BDC-NH2) MOF plays an important role in the capturing of CO2, and this contributes toward obtaining better photoelectrocatalytic efficiency of the CO2/methanol conversion compared to the use of the Cu/Cu2O and the non-functionalized Cu/Cu2O-Cu(BDC) MOF electrode.
Keywords: CO2 reduction; Cu(BDC-NH2) prepared by anodic deposition; MOF-based electrodes; Photoelectrocatalysis